KONTRIBUSI POWER OTOT TUNGKAI DAN KESEIMBANGAN TUBUH TERHADAP AKURASI TENDANGAN BEBAS PERMAINAN SEPAKBOLA SSB U-13 TIGA NAGA PEKANBARU - Saputra, Ardi Ansyah; Ramadi, Ramadi; Zainur, Zainur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on observations, it is clear that during training and matches it looks not optimal when scoring goals,this is evidenced at the time of the kick towards the goal, the resulting kick is not directed, not powerful and body position after making an innppropriate kick.In accordance with the background of the problem, this study aims to determine the contribution of leg muscle power and body balance to the accuracy of free kicks in the Tiga Naga Pekanbaru SSB u-13 soccer game. The population of this research in the Tiga Naga Pekanbaru SSB u-13 players totaling 18 people. Because the research sampling technique is saturated sampling.that is,researchers want to make generalizations with very small errors of less than 30 people.then the overall take of Tiga Naga Pekanbaru SSB u-13 players is a total population of 18 people.this research was carried out by the Tiga Naga Pekanbaru SSB u-13 soccer field on July 21,2018.the research data collection instrumen was a shoot test,leg muscle explosive test using broad jump standing and body balance using a modified bass test.data obtained and analyzed using a correlational rasearch design.based on the results of the research that the autor has described in the previous chapter,it can be concluded that there is contribution of leg muscle power to the accuracy of shooting on the Tiga Naga Pekanbaru SSB u-13.there is a contribution of the body’s balanceto the accuracy of shooting on the Tiga Naga Pekanbaru SSB u-13.then,there is a contribution of leg muscle power and body balance to the accuracy of shooting on the Tiga Naga Pekanbaru SSB u-13.Key Words: Leg Muscle Power, Body Balance, and Shooting Accuracy